From crisis to context: Reviewing the future of sustainable charcoal in Africa. (May 2022) - Branch, Adam; Agyei, Frank Kwaku; Anai, Jok Gai; Apecu, Stella Laloyo; Bartlett, Anne; Brownell, Emily; Caravani, Matteo; Cavanagh, Connor Joseph; Fennell, Shailaja; Langole, Stephen; Mabele, Mathew Bukhi; Mwampamba, Tuyeni Heita; et al.
Abstract: Is charcoal a sustainable energy source in Africa? This is a crucial question, given charcoal's key importance to urban energy. In today's dominant policy narrative – the charcoal-crisis narrative – charcoal is deemed incompatible with sustainable and modern energy, blamed for looming ecological catastrophe, and demanding replacement. However, an emerging sustainability-through-formalization narrative posits that charcoal can be made sustainable – specifically, through formalization of production, trade, markets, and consumption technologies. This represents an important opportunity to go beyond the crisis narrative and to engage productively with charcoal. However, this ascendent narrative also risks misrepresenting the reality of charcoal on the continent and leading to inappropriate policies. The narrative's designation of the African charcoal sector as unsustainable at present obscures charcoal production's diverse and uncertain impacts across the continent; moreover, the association of informality with unsustainability obscures a similarly complex and diverse social reality as well as the ways that social processes and relations of power and inequality determine charcoal's sustainability. We argue that charcoal needs to be considered within its historical, social, and environmental contexts to better understand its present and the emergent pathways to sustainable energy futures. We draw upon research that is raising questions about both the charcoal-crisis and the sustainability-through-formalization narratives to argue for a new narrative of charcoal in context . This approaches charcoal as a politically, ecologically, and historically embedded resource, entailing significant socio-ecological complexity across diverse historical and geographical conjunctures, and calling for new agendas of interdisciplinary research with an orientation towards sustainability and justice.